An Empirical Study of Paradigm Shift in Patient Loyalty Towards Hospitals in The Wake of the COVID-19 pandemic - Amit Kumar Nag; Bhumiphat Gilitwala (ACHSM, 2023)
Purpose: This research paper aims to identify the factors that have influenced patients' loyalty towards hospitals, doctors, or healthcare providers during the COVID-19 pandemic. The study seeks to create a comprehensive model that takes all these factors into account. Design/ Methodology/Approach: The study collected primary data from 400 valid responses using a Google Form, and a non-probability, convenient sampling technique was used. The sample size was calculated using G*Power  software. [21] The respondents were mostly from Bhopal or nearby areas in Madhya Pradesh, India. SmartPLS software [22] was used to conduct partial least square structural equation modeling. The study used confirmatory composite analysis to observe interrelationships in terms of linear compounds, and tested research hypotheses using a structural model. Findings: The COVID-19 pandemic has had a profound impact on the healthcare industry, including patient loyalty and expectations. The research highlighted that patients are increasingly looking for a more human-centered approach from medical staff, which includes better communication and more personalized care. This means that healthcare providers need to focus on building strong patient relationships based on trust, empathy, and respect. Originality Value: The present research work will help in identifying the key drivers of patient loyalty so that hospitals can focus on improving the areas that matter most to their patients, such as the quality of care, staff communication, accessibility, and overall patient experience. This, in turn, can increase patient satisfaction and ultimately lead to higher levels of patient loyalty.